2012
DOI: 10.3390/ijms13021561
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Structure and Functional Properties of Protein Concentrates and Isolates Produced from Walnut (Juglans regia L.)

Abstract: In this study, composition, structure and the functional properties of protein concentrate (WPC) and protein isolate (WPI) produced from defatted walnut flour (DFWF) were investigated. The results showed that the composition and structure of walnut protein concentrate (WPC) and walnut protein isolate (WPI) were significantly different. The molecular weight distribution of WPI was uniform and the protein composition of DFWF and WPC was complex with the protein aggregation. H0 of WPC was significantly higher (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
144
7
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(194 citation statements)
references
References 46 publications
39
144
7
4
Order By: Relevance
“…The major walnut proteins have MW ranges of around 30 _ 35 kDa and 18 _ 22 kDa, agreeing with the results by Mao and Hua (2012).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The major walnut proteins have MW ranges of around 30 _ 35 kDa and 18 _ 22 kDa, agreeing with the results by Mao and Hua (2012).…”
Section: Resultssupporting
confidence: 80%
“…Fig. 1 shows that the protein composition of walnut milk is the same as that of okara with a molecular weight (MW) range of 12 _ 55 kDa.The major walnut proteins have MW ranges of around 30 _ 35 kDa and 18 _ 22 kDa, agreeing with the results by Mao and Hua (2012).These results revealed that most of walnut protein (about 80%), including albumin, globulin, glutelin and prolamin, were dispersed into walnut milk although glutelin and prolamin were known to have poor aqueous solubility. Walnut milk was observed by microscope.…”
supporting
confidence: 79%
“…Based on the results above, the different H0 value might be due to the types of amino acids and the contents in each samples, such as more hydrophobic amino acids on the prolamin intramolecularly or little those of them extramolecularly and loosely. The present results were different from the relationship between the H0 and solubility, in which the higher H0 value was positive for the higher solubility as the concentrated walnut protein and isolate (Mao & Hua 2012). Those of not only the solubility was preference to the extramolecularly hydrophobic group, but also the balance of the hydrophobic and hydrophilic interaction that worked on this positive relationship.…”
Section: Resultscontrasting
confidence: 52%
“…After slowly stirring at 45°C for 2 h, the extraction was centrifuged at 4000 g for 20 min and then the supernatant was adjusted to pH 4.5 with 1 N HCl. The precipitated CRBP was collected, dialysed at 4°C for 48 h, and then freeze-dried (Mao & Hua 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The two most important species from the economic point of view are the Persian walnut (Juglans regia) appreciated for the quality of its nuts and the black walnut (Juglans nigra) highly prized for the quality of its timber. In South America, there are the following species: Argentinian walnut (Juglans australis), Bolivian walnut (Juglans boliviana), and black cedar (Juglans neotropica) found in Colombia, Venezuela, Peru, and Ecuador and known as tocte [1,2].…”
Section: Introductionmentioning
confidence: 99%